Inequality and Locational Determinants of the Distribution of Living Standards in India - Balasubramanian, Sriram; Kumar, Rishabh; Loungani, Prakash (Washington, D.C. : International Monetary Fund, 2021)
Using 2011-12 consumption micro-data, we find that nearly one-third of the variation in living standards in India can be explained by location alone. Consumption levels and locational inequality are positively related. In effect, from an individual's perspective, living standards are higher in richer, but more unequal, locations in India. The central factor behind these findings is the large difference in average consumption levels between rural and urban India and continued divergence in per-capita incomes between rich and poor states. Our results provide a possible explanation for the persistence of economic migration from rural to urban areas within a fast-growing emerging economy. While individuals cannot easily alter specific characteristics like their caste or religion, they have some freedom to change their location to enjoy better living standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Consumption; Dual-Sector Model; Inequality; Migration; Rural-Urban Gap; India